SPBT Management System for Sekolah Kebangsaan Pintas Puding using Role-Based Access Control (RBAC) - Shukur, Siti Aisyahtunnisa; Rahim, Nordiana (Applied Information Technology And Computer Science, 2026)
The Skim Pinjaman Buku Teks (SPBT), established in Malaysia in 1975, is a textbook loan program for government-assisted schools, ensuring students receive and maintain textbooks through organized borrowing, returning, and penalty processes. At Sekolah Kebangsaan Pintas Puding (SKPP), this is currently managed manually by a single SPBT teacher using Microsoft Word and Excel, leading to inefficiencies, errors, and increased costs, particularly during peak distribution periods. The SPBT Management System, a web-based application developed using the Waterfall Model with PHP and MySQL, automates textbook registration, tracking, and reporting with barcode technology, enhanced by Role-Based Access Control (RBAC) and password hashing for security. It supports SPBT Teachers, Class Teachers, and Pejabat Pendidikan Daerah (PPD) through modules for login, textbook and student management, and penalties. Functional and User Acceptance Testing (UAT) with these users confirmed all requirements were met, with feedback noting improved efficiency, reduced errors, and high usability. This system streamlines operations, reduces workload, and boosts accuracy and security at SKPP.